Alternative Polyadenylation and Differential Regulation of Ucp1: Implications for Brown Adipose Tissue Thermogenesis Across Species - Lu, Wen-Hsin; Chang, Yao-Ming; Huang, Yi-Shuian (Frontiers in Pediatrics, 2021)
Brown adipose tissue (BAT) is a thermogenic organ owing to its unique expression of uncoupling protein 1 (UCP1), which is a proton channel in the inner mitochondrial membrane used to dissipate the proton gradient and uncouple the electron transport chain to generate heat instead of adenosine triphosphate. The discovery of metabolically active BAT in human adults, especially in lean people after cold exposure, has provoked the “thermogenic anti-obesity” idea to battle weight gain. Because BAT can expend energy through UCP1-mediated thermogenesis, the molecular mechanisms regulating UCP1 expression have been extensively investigated at both transcriptional and posttranscriptional levels. Of note, the 3′-untranslated region (3′-UTR) of Ucp1 mRNA is differentially processed between mice and humans that quantitatively affects UCP1 synthesis and thermogenesis. Here, we summarize the regulatory mechanisms underlying UCP1 expression, report the number of poly(A) signals identified or predicted in Ucp1 genes across species, and discuss the potential and caution in targeting UCP1 for enhancing thermogenesis and metabolic fitness.